Atrial fibrillation induced by appropriate ventricular antitachycardia pacing in an ICD recipient. Issue 2 (August 2020) - Korantzopoulos, Panagiotis; Manolis, George
Abstract: In this short communication we briefly describe a 69-year-old man with dilated cardiomyopathy and an implantable cardioverter defibrillator who suffered a prolonged episode of palpitations. The interrogation of the device revealed an episode of ventricular tachycardia successfully treated with antitachycardia pacing. However, just before ventricular tachycardia termination, atrial fibrillation ensued. This specific proarrhythmic effect of antitachycardia pacing is concisely discussed. Retrograde conduction from the ventricles to the atria causing increased atrial pressures and mechano-electrical feedback, in the presence of a vulnerable atrial substrate, seems to be the most plausible mechanism. <Learning objective: Atrial fibrillation may be induced by antitachycardia pacing for ventricular tachycardia in vulnerable patients with an implantable cardioverter defibrillator. Although the incidence of this phenomenon seems to be rare it may have significant clinical impact and should be further studied.>